Diversidade sexual e homofobia na escola : as representações sociais de educadores/as da educação básica - Souza, Elaine de Jesus (2015)
The representations that educators have about the homophobic practices influence the construction or deconstruction of prejudices and discriminatory attitudes that are manifested in schools and end up causing many other types of violence throughout society. Thus, silencing and/or denial of multiple affective and sexual orientations that pervade the school contribute to the enhancement of prejudices. However, it is undeniable that, in most cases, teachers end up leaving out, rather than to adopt positions contrary to such violence, due to the lack of these issues in teacher education and the socio-cultural and religious norms that define their social representations. Thus, the main objective of this qualitative study was to analyze the social representations of educators about sexual diversity and homophobia, aiming to understand how such representations can influence and/or contribute to the construction or deconstruction of prejudice and discrimination that permeate the school environment. Therefore, we used the method of thematic categorical content and an instrument consisting of semi-structured interviews and questionnaires answered by 17 teachers from two schools in the basic education of a city of Sergipe was prepared. The results showed that social representations of most educators are guided by numerous doubts and contradictions about the thematic sexual diversity and homophobia because of ignorance due to the lack of these themes in the initial and continuing education, and other issues that impede the search for information and training, such as religious conventions, contributing to the maintenance of subtle and overt prejudices embedded in homophobic practices that permeate the school environment. And, most teachers reported situations of prejudice and discrimination that occurred at school, such as jokes, derogatory nicknames, exclusions, threats that make up the indirect homophobia. Thus, different behaviors of heteronormative pattern generate violence against individuals who are ridiculed, marginalized and judged within the school environment (and society in general). Therefore, to reveal the social representations (conceptions and experiences) educators about sexual diversity and homophobia, alert to the need for information and accurate and up to date on such issues formations. For teachers may question the heteronormative standards, understand, acknowledge and accept sexual and gender identities, deconstructing prejudice and effectively embracing this diversity of individuals that integrates school.